2008
DOI: 10.2105/ajph.2007.114769
|View full text |Cite
|
Sign up to set email alerts
|

I Think Therefore I Am: Perceived Ideal Weight as a Determinant of Health

Abstract: Muennig et al. | Peer Reviewed | Research and Practice | 501 RESEARCH AND PRACTICE  Objectives. We examined whether stress related to negative body image perception and the desire to lose weight explained some of the body mass index-health gradient.Methods. We used 2003 Behavioral Risk Factor Surveillance System data to examine the impact of desired body weight, independent of actual body mass index, on the amount of physically and mentally unhealthy days by race, ethnicity, and gender.Results. The differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 32 publications
2
88
4
2
Order By: Relevance
“…Gender differences in this study were similar to previous research indicating females had higher levels of body dissatisfaction and psychological distress (Eisenberg, Neumark-Sztainer, & Paxton, 2006;Lawler & Nixon, 2011;Santos, Richards, & Bleckley, 2007;von Soest & Wichstrøm, 2008) than males. Previous studies have indicated that body dissatisfaction and psychological functioning may contribute to obesity and negative health outcomes (Durso, Latner, & Ciao, 2016;Muennig, Jia, Lee, & Lubetkin, 2008;Wilson, Latner, & Hayashi, 2013). Our data showed no gender differences in WB contrary to other studies, where girls reported more WB than boys (Eisenberg, Neumark-Sztainer, Haines, & Wall, 2006;Neumark-Sztainer et al, 2002).…”
Section: Discussioncontrasting
confidence: 85%
“…Gender differences in this study were similar to previous research indicating females had higher levels of body dissatisfaction and psychological distress (Eisenberg, Neumark-Sztainer, & Paxton, 2006;Lawler & Nixon, 2011;Santos, Richards, & Bleckley, 2007;von Soest & Wichstrøm, 2008) than males. Previous studies have indicated that body dissatisfaction and psychological functioning may contribute to obesity and negative health outcomes (Durso, Latner, & Ciao, 2016;Muennig, Jia, Lee, & Lubetkin, 2008;Wilson, Latner, & Hayashi, 2013). Our data showed no gender differences in WB contrary to other studies, where girls reported more WB than boys (Eisenberg, Neumark-Sztainer, Haines, & Wall, 2006;Neumark-Sztainer et al, 2002).…”
Section: Discussioncontrasting
confidence: 85%
“…Research on weight 499 dissatisfaction (i.e., a subjective and affective self-evaluation based on oneÕs ideal versus actual 500 weight) similarly demonstrates how psychological perceptions and beliefs about oneÕs body can 501 have a stronger impact on indicators of health and well-being (e.g., blood pressure, onset of type 502 2 diabetes) than actual BMI status (Blake et al, 2013;Muennig, Jia, Lee, & Lubetkin, 2008; 503 Wirth et al, 2014;Wirth, Blake, Hebert, Sui, & Blair, 2015). 504…”
Section: Internalized Weight Stigma Moderates Eating Behavior 21mentioning
confidence: 99%
“…In a large study on prostate cancer patients treated with radical prostatectomy, androgen blockade-related symptoms were associated with a significantly higher likelihood of insomnia syndrome [20]. As insomnia and worsened body image perception are both notoriously linked to depression [21][22][23][24], they can concur in the development of depressive symptoms associated with low testosterone levels. These premises notwithstanding, study results on depression in prostate cancer patients undergoing ADT remain controversial: one pilot study found major depressive disorder in a high percent of prostate cancer patients under ADT [25], whereas a large population-based analysis of depressive and cognitive symptoms in patients with prostate cancer failed to show a higher prevalence of depressive symptoms in ADT treated patients vs. non-treated patients after adjusting for age, comorbidities, and disease stage [26].…”
Section: Introductionmentioning
confidence: 99%